Combined treatment with surgery and immune checkpoint inhibitor extended survival in a case of gastric intramural metastasis from esophageal cancer: a case report - Ayako Wakasugi; Yasue Kimura; Keita Natsugoe; Tomonori Nakanoko; Kentaro Nonaka; Sho Nambara; Qingjiang Hu; Ryota Nakanishi; Mitsuhiko Ota; Eiji Oki; Yoshinao Oda; Tomoharu Yoshizumi (Surgical Case Reports, 2023)
Abstract Background Intramural metastasis (IM) of esophageal cancer is classified as distant metastasis according to the Japanese Classification of Esophageal Cancer, and it is well-known to be associated with a poor prognosis. We herein report a case of perforated gastric IM of esophageal cancer that was successfully controlled with nonradical surgery and subsequent immune checkpoint inhibitor (ICI) treatment. Case presentation A 72-year-old woman was referred to our department for the treatment of esophageal cancer and perforated gastric ulcer. A histological examination of the main tumor and gastric ulcer lesion revealed squamous cell carcinoma. Since the gastric wall tumor had invaded the celiac artery, complete resection was considered impossible. Chemotherapy was administered but led to severe adverse events, so palliative resection was performed. Two months after surgery, computed tomography revealed enlargement of the residual tumor around the celiac artery. However, after nivolumab monotherapy was started, the tumor diminished remarkably, and the quality of life of the patient dramatically improved. Nine months after nonradical surgery, she is surviving without any disease concern. Conclusions With the increased availability of ICIs, multidisciplinary treatment with surgery and ICIs can potentially lead to long-term survival, even in cases expected to have a poor prognosis.